METODE PEMBELAJARAN DAN SIKAP MAHASISWA TERHADAP HASIL BELAJAR BAHASA INDONESIA - Retna Ningsih (Faktor Jurnal Ilmiah Kependidikan, 2014)
Abstract: Determine the effect of differences in teaching methods and learning methods conventional CTL against Indonesian student learning outcomes; determine the effect of the interaction between learning method (CTL / conventional) and the attitude of students towards learning outcomes Indonesian; know differences in learning outcomes Indonesian students who were taught using learning methods CTL using conventional learning methods in a group of students who have a positive attitude; determine differences in learning outcomes Indonesian students who were taught using learning methods CTL using conventional learning methods on a group of students who have a negative attitude Keywords: Learning, Attitude and Learning Outcomes